Quantifying the Impact of Renewable Energy Research on Environmental Sustainability - Bambang Winardi; Ajub Ajulian ZM (West Science Interdisciplinary Studies, 2023)
The imperative of addressing environmental sustainability and energy security has propelled extensive research into renewable energy technologies. This study employs bibliometric analysis to explore the impact of renewable energy research on environmental sustainability. Utilizing data from Web of Science and Scopus, a comprehensive dataset of scholarly articles and patents was compiled. The methodology involves keyword formulation, citation analysis, and collaboration network evaluation, supplemented by VOSviewer analysis for network visualization. The analysis unveils thematic clusters, influential citations, and keyword occurrences, unravelling the multifaceted nature of renewable energy research. Six thematic clusters emerge, encompassing biomass utilization, climate change, economic growth, efficiency optimization, energy systems, and energy consumption. Key citations provide insights into modeling techniques, sustainability indicators, and environmental assessment methodologies. Frequent keywords, such as life cycle assessment and technology, underscore the core pillars of the field, while less frequent terms like climate change and electricity highlight vital concepts. The findings provide holistic insights into the growth, impact, and interconnections within renewable energy research, offering valuable guidance for policymakers, researchers, and stakeholders committed to advancing environmental sustainability through renewable energy solutions.